2003
DOI: 10.1590/s0100-879x2003000200015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of liposome-encapsulated antimony in dogs

Abstract: The achievement of complete cure in dogs with visceral leishmaniasis is currently a great challenge, since dogs are the main reservoir for the transmission of visceral leishmaniasis to humans and they respond poorly to conventional treatment with pentavalent antimonials. In order to improve the efficacy of treatment, we developed a novel formulation for meglumine antimoniate based on the encapsulation of this drug in freeze-dried liposomes (LMA). The aim of the present study was to evaluate the biodistribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…Furthermore, we have reported the distribution of antimony (Sb) in healthy dogs, following a single intravenous (iv) bolus injection of LMA. The latter study suggested that the critical organ for the treatment with LMA could be the bone marrow, since it showed very low antimony levels (5), and that a multiple dose regimen would be required to achieve therapeutic levels of antimony in this tissue. On the other hand, the impact of infection on the capture of liposomes by this tissue has not yet been documented.…”
Section: Da Schettini Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we have reported the distribution of antimony (Sb) in healthy dogs, following a single intravenous (iv) bolus injection of LMA. The latter study suggested that the critical organ for the treatment with LMA could be the bone marrow, since it showed very low antimony levels (5), and that a multiple dose regimen would be required to achieve therapeutic levels of antimony in this tissue. On the other hand, the impact of infection on the capture of liposomes by this tissue has not yet been documented.…”
Section: Da Schettini Et Almentioning
confidence: 99%
“…Meglumine antimoniate was encapsulated in freeze-dried liposomes as previously described (4,5). Briefly, small unilamellar vesicles were prepared in water from L-α-distearoylphosphatidylcholine, cholesterol and dicetylphosphate (molar ratio of 5:4:1) at a final lipid concentration of 55 g/L.…”
Section: Da Schettini Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos de biodistribuição/farmacocinética do antimônio em camundongos e cães mostraram que a forma lipossomal promove níveis de antimônio muito mais elevados e prolongados no fígado e no baço dos animais quando comparado à forma livre 21,22 . Essa diferença de biodistribuição entre as formas livre e encapsulada é ilustrada, na Tabela 2, a partir de dados obtidos em cães.…”
Section: Figura 4 Destino Dos Lipossomas Convencionais Por Via Endovunclassified
“…Vale ressaltar que o tamanho dos lipossomas é um parâmetro importante, pois tem influência tanto na taxa de eliminação do parasita 23 , quanto na concentração de antimônio ao nível da medula ós-sea 22 . Portanto, lipossomas pequenos (diâmetro < 200 nm) parecem ter acesso facilitado à medula óssea, o que é de interesse pois devem possibilitar a eliminação do parasita que se encontra nesse tecido.…”
Section: Figura 4 Destino Dos Lipossomas Convencionais Por Via Endovunclassified